Efektivitas Perlindungan Hukum terhadap Anak sebagai Korban Kekerasan Seksual Berdasarkan UU No. 35 Tahun 2014 Tentang Perlindungan Anak - Diki Abdul Hamid; Ahmad Yunus; Dairani Dairani (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
This study aims to analyze the effectiveness of legal protection for children as victims of sexual violence based on Law Number 35 of 2014 concerning Child Protection. Sexual violence against children constitutes a serious violation of human rights and has long-term impacts on the physical, psychological, and social development of victims. Normatively, the law regulates various forms of protection, including prevention, handling, rehabilitation, and the imposition of stricter sanctions against perpetrators. However, in practice, several obstacles remain in the implementation of such legal protection. This research employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources analyzed qualitatively through legal interpretation techniques. The analysis evaluates the conformity between the legal norms stipulated in the legislation and their implementation in practice. The results indicate that, normatively, Law Number 35 of 2014 provides a relatively comprehensive legal framework for protecting child victims of sexual violence. Nevertheless, its effectiveness is hindered by challenges such as law enforcement issues, limited facilities and infrastructure, lack of inter-agency coordination, and social stigma toward victims. Therefore, strengthening policy implementation and enhancing synergy among stakeholders are necessary to ensure optimal legal protection for children as victims of sexual violence.